THE IMPORTANCE OF THE WORKS OF ALEXANDER FEINBERG IN UZBEK LITERATURE - Maftuna Abdurasulova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This article is about Alexander Feinberg, one of the most prominent and talented poets of his time. Uzbekistan is a prosperous country, where creativity, knowledge, compassion prevail, and which believes that its children will grow up to be a harmoniously developed generation, creating a solid foundation for this. Alexander Feinberg, the owner of a great heart lived and worked in this blessed land. The article discusses the analysis of Feinberg`s works, its role and significance in Uzbek literature. There are also short excerpts frominterviews with the poet.